2021
DOI: 10.1017/dmp.2021.346
|View full text |Cite
|
Sign up to set email alerts
|

Explore the Approaches to Corporate Social Responsibility Implemented by E-Commerce Platforms in China During the Early Stage of COVID-19: A Mixed-Methods Content Analysis

Abstract: Objectives: To explore (a) the approaches to corporate social responsibility (CSR) implemented by e-commerce platforms in China during the early stage of COVID-19 (ESCOVID-19) and; (b) the factors associated with the platforms’ choice of these approaches. Methods: We collected the CSR data from the Internet during ESCOVID-19. Conventional content analysis was used to develop the targeted approaches. Finally, based on the frequency analysis of each approach, rank-based nonparametric testi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…That is why, an improvement in the quantitative characteristics of HRM, in particular, an increase in the number of jobs, is undesirable or even unattainable in e-commerce. A more preferable alternative is an increase in the quality of HRM, which stimulates humanization of corporate social responsibility—in this case, labor efficiency is improved, the quality of service is raised, customers’ loyalty grows, and the volume of sales and revenues of e-commerce companies takes place, while their expenditures for personnel remain unchanged (Vuong and Bui, 2023 ; Zhang et al, 2023 ). Thanks to this, the humanization of corporate social responsibility in e-commerce is characterized by high effectiveness not only from the social but also from the financial and economic position.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…That is why, an improvement in the quantitative characteristics of HRM, in particular, an increase in the number of jobs, is undesirable or even unattainable in e-commerce. A more preferable alternative is an increase in the quality of HRM, which stimulates humanization of corporate social responsibility—in this case, labor efficiency is improved, the quality of service is raised, customers’ loyalty grows, and the volume of sales and revenues of e-commerce companies takes place, while their expenditures for personnel remain unchanged (Vuong and Bui, 2023 ; Zhang et al, 2023 ). Thanks to this, the humanization of corporate social responsibility in e-commerce is characterized by high effectiveness not only from the social but also from the financial and economic position.…”
Section: Resultsmentioning
confidence: 99%
“…In their turn, Zhang et al ( 2023 ) noted the increased role and proved the anti-crisis effect of the corporate social responsibility practices, which were implemented by e-commerce platforms in China at the early stage of the COVID-19 pandemic. Wang and Yang ( 2021 ) proved that corporate social responsibility makes rural consumers change their attitude toward e-commerce and start using it actively, preferring it to offline purchases in the markets of dynamically developing countries.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The awareness of management for the achievement of organizational goals is the way forward to success in organizational performance. The stable working of an organization for the sustainability of the environment is the way forward to achieving organizational goals for environmental sustainability [ 12 ]. The regulations of the government used for advancement of organizational work can become better strategies to improve organizational performance productively.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Furthermore, Hsiao, Jiang [ 11 ] reported that the advanced working of the organization sector and improved performance of employees with efficiency can be a way forward to achieve sustainability in the environment. Many firms are working to advance their performance to achieve organizational sustainability which is necessary for the productive performance of organizations [ 12 , 13 ]. Firm performance for environmental sustainability depends on different factors, and organizational sustainability is also one of these factors [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…By acting as a buffer for organisational adaptation, slack has been used to absorb the environmental variation and disruption caused by COVID-19 (Li, 2021). CSR activities represent one of the most important means of addressing the problems caused by COVID-19 (Zhang et al, 2021). Previous studies have identified that slack resources are allocated to CSR activities and companies with more slack resources are more inclined to conduct CSR (Shahzad et al, 2016;Zhang et al, 2020;Lu et al, 2022).…”
Section: Slack Resources In the Covid-19 Eramentioning
confidence: 99%